The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1210/jc.2012-3592
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Vitamin D Status of Vitamin D Deficient Adults Is Associated With Improved Mitochondrial Oxidative Function in Skeletal Muscle

Abstract: Objective: Suboptimal mitochondrial function has been implicated in several disorders in which fatigue is a prominent feature. Vitamin D deficiency is a well-recognized cause of fatigue and myopathy. The aim of this study was to examine the effects of cholecalciferol therapy on skeletal mitochondrial oxidative function in symptomatic, vitamin D-deficient individuals.Design: This longitudinal study assessed mitochondrial oxidative phosphorylation in the gastrosoleus compartment using phosphorus-31 magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
173
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 23 publications
12
173
1
Order By: Relevance
“…The differentially expressed mRNAs encode proteins that play significant roles in multiple biochemical pathways involved in muscle contraction and relaxation; extracellular matrix-cell receptor interactions; actin cytoskeleton remodeling; and JAK-STAT, insulin-like (17) 0.014 Reactome p53 pathway (16) 0.014 Panther Interferon-signaling (11) 0.017 Panther Muscle contraction (9) 0.022 Reactome Terpenoid backbone biosynthesis (6) 0.028 KEGG Cell adhesion molecules (24) 0.048 KEGG (27), which showed that treatment of vitamin D-deficient humans with cholecalciferol improves muscle phosphocreatine recovery after exercise, suggesting an effect of 1␣,25(OH) 2 D 3 on the formation of high energy phosphorylated intermediates and mitochondrial function. The increase in the numbers of mitochondria could also account for the increase in cellular OCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentially expressed mRNAs encode proteins that play significant roles in multiple biochemical pathways involved in muscle contraction and relaxation; extracellular matrix-cell receptor interactions; actin cytoskeleton remodeling; and JAK-STAT, insulin-like (17) 0.014 Reactome p53 pathway (16) 0.014 Panther Interferon-signaling (11) 0.017 Panther Muscle contraction (9) 0.022 Reactome Terpenoid backbone biosynthesis (6) 0.028 KEGG Cell adhesion molecules (24) 0.048 KEGG (27), which showed that treatment of vitamin D-deficient humans with cholecalciferol improves muscle phosphocreatine recovery after exercise, suggesting an effect of 1␣,25(OH) 2 D 3 on the formation of high energy phosphorylated intermediates and mitochondrial function. The increase in the numbers of mitochondria could also account for the increase in cellular OCR.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggest that the vitamin D receptor (VDR) is expressed in skeletal muscle (20 -24), and VDR deletion in mice results in alterations in muscle function and strength (25,26). Treatment of vitamin D-deficient humans with cholecalciferol improves muscle phosphocreatine recovery after exercise (27), suggesting that vitamin D 3 or its metabolites alter skeletal muscle oxidative capacity.…”
mentioning
confidence: 99%
“…They involve the rapid regulation of membrane calcium channels, suggesting a role for vitamin D in the calcium‐mediated muscle functions, such as muscle contraction and mitochondrial function, which leads to an adequate insulin signalling and muscle substrate metabolism 42. All these findings may clarify the relationship between low vitamin D status and muscle weakness,37, 43 intramuscular fat deposition,44 and resistance to insulin,45 which is related to cardiovascular risk and increased skeletal muscle breakdown 46.…”
Section: Vitamin D Physiologymentioning
confidence: 98%
“…Very recently the beneficial effect of vitamin D on oxidative phosphorylation was shown, giving a clue for the possible mechanism of vitamin D associated fatigue and muscle weakness [13].…”
Section: Discussionmentioning
confidence: 99%